Examining EFL Undergraduate Students’ Constraints in Research Proposal Writing: A CLA Perspectives - Eka Fajar Rahmani (Universitas Pendidikan Ganesha, 2025)
Students often struggle with organizing proposal sections, understanding research concepts, and managing time. These obstacles interfere with their academic development and emphasize the importance of a deep understanding of the underlying constraints. This research aims to investigate how individual, task, and environmental constraints interact and contribute to such challenges. This research utilizes a survey study with a quantitative framework. A quantitative survey was conducted on 91 seventh-semester students from the English Education study program. Data were collected through a standardized questionnaire that measured students' level of confidence, experience, and understanding in writing a research proposal. Descriptive statistical analysis was used to identify the dominant problems in each CLA dimension. The results showed that more than 60% of the students experienced difficulties in conducting a literature review, while 50% felt afraid of making mistakes, which highlighted significant cognitive and psychological barriers. In addition, 43.33% faced task-related difficulties, such as balancing proposal sections, and 42.22% reported time management issues. These interrelated obstacles indicate the need for holistic interventions, such as workshops on task management, literature review strategies, and peer support to improve students' research skills.